I) \( [2+(26 \div 2+4 \times 3)-(15 \div 3 \times 2)] \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the expression step by step, let's break it down: First, we handle the divisions and multiplications: 1. \( 26 \div 2 = 13 \) 2. \( 4 \times 3 = 12 \) 3. \( 15 \div 3 = 5 \) 4. \( 5 \times 2 = 10 \) Now, substituting these values back into the expression gives us: \[ 2 + (13 + 12 - 10) \] Now, simplifying the parentheses: 1. \( 13 + 12 = 25 \) 2. \( 25 - 10 = 15 \) Finally, we add this result to 2: \[ 2 + 15 = 17 \] So, the final answer is **17**!